'I'm here to save my life': a qualitative study of experiences navigating a cryotherapy referral system for human papillomavirus-positive women in western Kenya. Issue 7 (24th July 2019) - Huchko, Megan; Adewumi, Konyin; Oketch, Sandra; Saduma, Ibrahim; Bukusi, Elizabeth
Abstract : Background: We sought to understand the beliefs, social norms and logistical factors that affect human papillomavirus (HPV)-positive women's uptake of cryotherapy treatment as part of a two-part cervical cancer screening strategy in rural Kenya. Methods: In-depth interviews within a parent cluster-randomised trial. Setting: Government-run county hospital in western Kenya. Participants: 273 of 372 (73.4%) HPV-positive women who underwent cryotherapy Results: Many women feared that an HPV infection meant they would develop cancer. Almost all women reported initial fear of the treatment procedure, followed by a more positive experience than anticipated. Lacking funds for transportation to the treatment site was the most common barrier. Women felt that decentralised treatment would be the most important facilitator of greater access. Spousal encouragement and financial support were key facilitators of treatment access, however many women felt that other husbands in the community would not be supportive. Women described successfully acquiring treatment as empowering, and almost all would recommend seeking cryotherapy to other women who test HPV-positive. Most felt eager to share their own experiences with others to encourage treatment. Conclusions: The main facilitators of treatment access were understanding of the health risks and sense of empowerment. A decentralised treatment model or transportation support may facilitate access, along with improved health messaging about HPV infection, cancer and the treatment process. Focusing on women's personal feelings of empowerment may further improve uptake and satisfaction. These data will be used to design a strategy to improve linkage to treatment. Trial Registration: NCT02124252 .